Antibody–drug conjugates in patients with advanced/metastatic HER2-low-expressing breast cancer: a systematic review and meta-analysis - Isabella Michelon; Maria Inez Dacoregio; Maysa Vilbert; Jonathan Priantti; Caio Ernesto do Rego Castro; Lucas Vian; Paolo Tarantino; Evandro de Azambuja; Ludimila Cavalcante (Therapeutic Advances in Medical Oncology)
Background: Until recently, targeted therapies have failed to benefit patients with human epidermal growth factor receptor 2 (HER2)-low-expressing breast cancer (BC). Nevertheless, antibody–drug conjugates (ADCs) have reshaped their prognosis. Objectives: We performed a systematic review and meta-analysis to assess the effectiveness of ADCs in patients with HER2-low advanced/metastatic (a/m) BC. Design: This study is a systematic review and meta-analysis. Data sources: We searched PubMed, Embase, and Cochrane databases as well as the American Society of Clinical Oncology, European Society for Medical Oncology, and San Antonio Breast Cancer Symposium conference proceedings. Methods: Studies evaluating ADCs (trastuzumab deruxtecan (T-DXd), sacituzumab govitecan (SG), MRG002, and RC48-ADC) in patients with HER2-low a/mBC were included. We used R software (v.4.2.2) and random effects models for all analyses. Heterogeneity was assessed using the I 2 test. Results: Overall, 14 studies were included (five real-world studies and nine clinical trials (CTs)), with 2883 HER2-low a/mBC patients: 808 received treatment of physician’s choice (TPC), and 2075 ADCs. Most were treated with T-DXd ( n  = 1691), followed by SG ( n  = 310), MRG002 ( n  = 56), and RC48-ADC ( n  = 18). Patients treated with T-DXd achieved a significantly higher objective response rate (ORR), disease control rate (DCR), and clinical benefit rate (CBR) than those receiving other ADCs. In the pooled analysis of four randomized CTs, ADCs statistically prolonged progression-free survival ( n  = 1828, hazard ratio (HR) 0.50, 95% confidence interval (CI) 0.36–0.68, I 2  = 82%, p  < 0.001) and overall survival ( n  = 1546, HR 0.70, 95% CI 0.57–0.86, I 2  = 43%, p  < 0.001) compared with TPC. Patients on ADCs also achieved a greater antitumor response than TPC, including better ORR (odds ratio (OR), 3.7, 95% CI 2.5–5.6, I 2  = 59%, p  < 0.001), DCR (OR, 2.7, 95% CI 2.1–3.5, I 2  = 0%, p  < 0.001), and CBR (OR, 3.6, 95% CI 2.6–5.2, I 2  = 56%, p  < 0.01). Conclusion: Our systematic review and meta-analysis confirms the efficacy of ADCs in HER2-low a/m BC patients over TPC. Future studies should focus on bringing ADCs into earlier lines of therapy in this population. Trial registration: This study was registered in PROSPERO (CRD42024452962).